EFFECT OF HEAT STRESS ON HAEMATOLOGICAL AND IMMUNOLOGICAL PARAMETERS IN BROILER CHICKEN - Kumar, Ravi; Kinehar, Amol S; Ingle, VC; Sonkusale, Prashant; Kumar, Vipin (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Environmental stress negatively affects health condition and immunity of broiler birds. The study was envisaged to understand the effect of heat stress on haematological and immunological parameters in broiler chicken under commercial production system. During summer season significant (P
Keywords: Broiler; Haematology; Heat Stress; Immunity